Alleviating Poverty in Indonesia through Zakat during the Period 2019–2023 - Yogi Afrianto (Jurnal Ilmiah Multidisiplin, 2025)
Zakat is a portion of an individual's wealth that must be paid out of their possessions because it contains the rights of others that must be given or purified. History demonstrates the power of zakat in alleviating poverty between 717 and 720 AD during the reign of the Caliph Umar bin Abdul Aziz. In Indonesia, the poverty rate remains high, with 23.85 million people still trapped in poverty. One approach the Indonesian government can take is to optimize zakat receipts and then distribute them appropriately and professionally. Through zakat, poverty will be reduced and economic activity in society will increase. Furthermore, the Indonesian government already has Zakat Collection Institutions (Amil Zakat) and Zakat Agencies (Bandung Amil Zakat). The government's task is to develop policies and procedures for these existing zakat institutions to eradicate poverty from Indonesia. Research shows that zakat plays a significant role in wealth redistribution and poverty reduction. However, challenges in zakat collection and distribution require careful monitoring to ensure compliance with regulations and ensure zakat's effectiveness.